Exploring Students’ Misconception in the Frame of Graphic and Figural Representation on Projectile Motion Regarding to the COVID-19 Constraints - Wahyu Hidayatulloh; Heru Kuswanto; Purwoko Haryadi Santoso; Eko Susilowati; Zul Hidayatullah (STKIP Singkawang, 2021)
Remote learning has reformed the normal tradition of physics instruction in the existence of COVID-19 pandemic. The previous documentation of student’s misconception is mostly discovered in the normal condition of physics instruction. Regarding to the pandemic outbreak is necessary since distance learning routines have absolutely influence the physics education outcomes all over the world. To explore the issues, this quantitative study has descriptively identified students' misconception on projectile motion in the frame of graphic and figural representations. The six items of Busyairi and Zuhdi’s three tier test were administered to the 76 students in a Javanese public high school, Indonesia. Overall, the Arslan, Cigdemolu, & Moseley’s categorical framework classified that the whole participants still congregate in the misconception’s groups on projectile motion. The lack of students’ representation on projectile motion might be magnified by the pandemic restrictions in providing appropriate visualization on projectile concept. Finally, the author suggested that the alternative of online learning during the outbreak have not yet been effectively engaged to promote the physics representation on projectile motion.